Runemarks - Harris, Joanne, 1964- (London : Corgi, 2012)
Maddy Smith, who bears the mysterious mark of a rune on her hand, learns that she is destined to join the gods of Norse mythology and play a role in the fate of the world.
6.5
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Mythology, Norse -- Juvenile fiction; Fantasy; Magic -- Fiction; Mythology, Norse -- Fiction; Magic -- Fiction; Norse mythology -- Fiction; Fantastic fiction; Fantastic fiction